Moral Branding and Muslim Consumer Agency: A Study of Purchase Behavior Toward Israel-Affiliated Halal Products - Farchina, Very Alfi; Rusyida, Wilda (Indonesian Journal of Islamic Literature and Muslim Society, 2025)
The ongoing Israel–Palestine conflict has triggered global repercussions, including the emergence of boycott movements against products affiliated with Israel. This phenomenon has influenced the consumption patterns of Muslim communities, particularly Generation Z, who demonstrate high social awareness and are deeply connected to digital media. This study aims to analyze the influence of brand image, brand experience, and brand ambassador on the purchasing decisions of halal products associated with Israeli affiliations among Generation Z in Pekalongan Regency. A quantitative approach was employed, involving 100 purposively selected respondents. Data were analyzed through validity and reliability tests, multiple linear regression, and classical assumption tests using EViews 10 software. The results show that brand image and brand ambassador have a significant partial influence on purchasing decisions, while brand experience does not. Simultaneously, all three variables exert a significant influence, with an Adjusted R² value of 46.1%. These findings highlight that ethical and social awareness play a crucial role in Generation Z’s purchasing decisions, outweighing functional brand experience alone. The implications of this study emphasize the importance of brand communication strategies that are sensitive to geopolitical issues and aligned with the moral values of Muslim consumers.